Prioritizing the nine challenges of Malaysian Vision 2020 - Islam, Rafikul (2011)
The exotic phrase “Vision 2020” has been coined to signify a lofty and long term objective pertaining to some issue in many countries across the world. In Malaysia, the architect of this vision is the former Prime Minister Tun Dr. Mahathir bin Mohamad, who unveiled it in 1991, 30 years in advance of the time line of demarcation. The gist of the Malaysian Vision 2020 is that “By the year 2020, Malaysia will become a developed nation.” In course of this long, arduous and turbulence full journey, the nation needs to address the nine strategic challenges: (1) Establishing a united Malaysian nation, (2) Creating a psychologically liberated, secure, and developed Malaysian society, (3) Developing a mature democratic society, (4) Forming a community that has high morale, ethics, and religious strength, (5) Establishing a mature, liberal and tolerant society, (6) Establishing a scientific and progressive society, (7) Establishing a fully caring society, (8) Ensuring an economically just society, and (9) Establishing a prosperous society. Malaysia has already made a significant progress in achieving the objectives of Vision 2020. Nonetheless, depending upon the prevailing as well as ensuing situation, a number of new action plans need to be devised and implemented before the country is declared as a developed nation. In this context, the present paper applies the Analytic Hierarchy Process to prioritize the above-mentioned nine challenges so that the country’s scarce resources can be disbursed to formulate and implement the right action plans in the remaining ten years.